The nature of electron lone pairs in BiVO4 - Payne, D; Robinson, M; Egdell, R; Walsh, A; McNulty, J; Smith, K; Piper, L (2011)
The electronic structure of BiVO4 has been studied by x-ray photoelectron, x-ray absorption, and x-ray emission spectroscopies, in comparison with density functional theory calculations. Our results confirm both the direct band gap of 2.48 eV and that the Bi 6s electrons hybridize with O 2p to form antibonding "lone pair" states at the top of the valence band. The results highlight the suitability of combining s2 and d0 cations to produce photoactive ternary oxides. © 2011 American Institute of Physics.